Diagnostic capability of long-term electrocardiographic telemonitoring for detection of heart rhythm disorders - Berdnyk, Inna; Bogomaz , Volodymyr; Dolyna , Tetiana; Onofriichuk , Yevhen (The Ukrainian Scientific Medical Youth Journal, 2024)
prevalence of cardiac rhythm and conduction disorders is increasing and associated with the growing amount of people of older age groups. The extended use of traditional electrocardiography (ECG) recorders is currently limited due to duration of the investigation, possible skin irritation and withdrawal of consent by the patients. The aim: evaluation of the frequency of arrythmia incidents in adult patients of different ages by assessing the patch monitoring results, and the impact of the monitoring duration on the possibility of diagnosis. Materials and methods: study included 1123 patients aged from 18 to 99 (599 women and 524 men), data about whom was collected in 2021-2022. ECG was recorded by the «Mawi Heart patch» – a single-use dual-channel device for continuous ECG recording for up to2 7 days. Results: the average ECG monitoring time was 81,03±18,5 hours or 3,37±0,7 days. The majority of the participants (74,35%) received the continuous 3-day ECG monitoring. Most rhythm disorders were recorded in the first 24 hours, but over the next 2 days, atrial fibrillation (AF) was detected in 7,66%, more often in men (48 participants, p=0,048) and with some differences in age groups. Starting above 50 years of age, the frequency of AF diagnosing on the first monitoring days is decreased and it is significantly statistically lower (61,11%, p<0,05). Three-day ECG monitoring is associated with a higher chance of detecting AF (OR=2,03; 1,53-3,02, p=0,031) regardless of gender, while the 5-day monitoring wasn’t as effective. The prolonging of the monitoring time increased the number of diagnosed supraventricular tachycardia (SVT) cases by 5,53% in men and 8,35% in women. The 3 days of monitoring are associated with a higher chance of SVT detection (OR = 4,18; 3,32–4,95, p=0,009). There is a direct correlation between SVT detection and the older age groups (r=0,53, p<0,05). SVT detection is higher in patients of 71-80 years old (OR = 2,71; 2,35–3,75, p=0,0041), and of 81-99 years (OR = 2,92; 2,56–3,49, p=0,0039). Conclusion: The frequency of arrhythmia detection, in patients referred to long-term patch monitoring, is high both for AF and SVT. The sex and age patterns for the prevalence of the described arrhythmias were statistically confirmed. The use of long-term ECG patch monitoring increases the chance of arrhythmia detection, primarily for older patients.